2016
DOI: 10.3171/2016.4.peds1698
|View full text |Cite
|
Sign up to set email alerts
|

Variation in seizure prophylaxis in severe pediatric traumatic brain injury

Abstract: OBJECTIVE Posttraumatic seizure is a major complication following traumatic brain injury (TBI). The aim of this study was to determine the variation in seizure prophylaxis in select pediatric trauma centers. The authors hypothesized that there would be wide variation in seizure prophylaxis selection and use, within and between pediatric trauma centers. METHODS In this retrospective multicenter cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…7 Other research has identified levetiracetam, phenobarbital, and valproic acid for EPTS prophylaxis in addition to phenytoin and fosphenytoin. 19,20 In a 2016 publication evaluating the use of levetiracetam for EPTS prophylaxis, the authors reported 17% of patients having EPTS with levetiracetam, which was higher than reported EPTS with phenytoin. 21 However, since the studies in this review were often not specific about the agents used, the purpose of these antiseizure agents (i.e., reduction in ICP or antiseizure prophylaxis) is often unclear in this setting.…”
Section: Discussionmentioning
confidence: 96%
“…7 Other research has identified levetiracetam, phenobarbital, and valproic acid for EPTS prophylaxis in addition to phenytoin and fosphenytoin. 19,20 In a 2016 publication evaluating the use of levetiracetam for EPTS prophylaxis, the authors reported 17% of patients having EPTS with levetiracetam, which was higher than reported EPTS with phenytoin. 21 However, since the studies in this review were often not specific about the agents used, the purpose of these antiseizure agents (i.e., reduction in ICP or antiseizure prophylaxis) is often unclear in this setting.…”
Section: Discussionmentioning
confidence: 96%
“…Considering the high incidence of seizure in infantile TBI, an aggressive approach is needed to prevent early seizure in TBI in infants. Role of antiepileptic drug (AED) in pediatric PTE is not definitely determined 5 , 23) . However, many authors report the effectiveness of AED to prevent early seizure 11 , 19 , 21) .…”
Section: Discussionmentioning
confidence: 99%
“…(6) Another recently published retrospective study of data from five centers reported an even higher rate of seizure prophylaxis, 79%. (9) Many (61.8%) of the children who received AEDs in our study received them on day 0 of the hospitalization, likely indicating prophylactic use. Similar to EEG monitoring, children with known risk factors for PTS were particularly likely to receive AEDs, as both child abuse and SDH were associated with AED use earlier in the hospitalization.…”
Section: Discussionmentioning
confidence: 76%
“…A recent retrospective analysis of children with severe TBI at five regional pediatric trauma centers concluded that 79% received seizure prophylaxis with AEDs, 63% of those within 24 hours of injury. (9) In a survey of 43 sites participating in a large observational cohort study, 90% of sites reported seizure prophylaxis with AEDs in children with severe TBI. (10) The same survey also reported wide center variation in approach to EEG monitoring.…”
Section: Introductionmentioning
confidence: 99%